2016
DOI: 10.1152/ajprenal.00297.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Glt1 glutamate receptor mediates the establishment and perpetuation of chronic visceral pain in an animal model of stress-induced bladder hyperalgesia

Abstract: Psychological stress exacerbates interstitial cystitis/bladder pain syndrome (IC/BPS), a lower urinary tract pain disorder characterized by increased urinary frequency and bladder pain. Glutamate (Glu) is the primary excitatory neurotransmitter modulating nociceptive networks. Glt1, an astrocytic transporter responsible for Glu clearance, is critical in pain signaling termination. We sought to examine the role of Glt1 in stress-induced bladder hyperalgesia and urinary frequency. In a model of stress-induced bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…In addition, a longer VMR duration in WAS rats represents a longer sensory/pain response to bladder stimuli. A lower sensory threshold may explain the previously documented increases in urinary frequency in this animal model . This is consistent with our previous publications, which demonstrates that the increased urinary frequency in rats exposed to WAS is associated with bladder hyperalgesia .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, a longer VMR duration in WAS rats represents a longer sensory/pain response to bladder stimuli. A lower sensory threshold may explain the previously documented increases in urinary frequency in this animal model . This is consistent with our previous publications, which demonstrates that the increased urinary frequency in rats exposed to WAS is associated with bladder hyperalgesia .…”
Section: Discussionsupporting
confidence: 93%
“…A lower sensory threshold may explain the previously documented increases in urinary frequency in this animal model. 7,8,13 This is consistent with our previous publications, which demonstrates that the increased urinary frequency in rats exposed to WAS is associated with bladder hyperalgesia. 8 The WAS-induced bladder hypersensitivity is similar to other reports regarding different stress animal models.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A recent study using an animal model of stress‐induced hyperalgesia revealed that exogenous glial glutamate transporter‐1 GLT‐1 upregulation via intraperitoneal CTX injection inhibited development and reversed pre‐existing pain and voiding dysfunction induced by water avoidance stress . Our studies also showed that GLT‐1 overexpression attenuates visceral nociception of the VMR to bladder distension and both local irritant‐induced and cross‐organ‐sensitized VMR to bladder distension or by neonatal colonic insult .…”
Section: Discussionsupporting
confidence: 66%